Applying a Digital Health Checklist and Readability Tools to Improve Informed Consent for Digital Health Research - Nebeker, Camille; Gholami, Maryam; Kareem, Daniah; Kim, Emily (Frontiers in Digital Health, 2021)
Background: As research involving human participants increasingly occurs with the aid of digital tools (e.g., mobile apps, wearable and remote pervasive sensors), the consent content and delivery process is changing. This paper describes a process of developing a “meaningful consent” document for a study that involved that use of body worn sensors to capture natural behaviors in the wild. Methods: A consent document approved by a US institutional review board was deconstructed into segments that aligned with federal requirements for informed consent. Three researchers independently revised each segment of text with a goal of achieving a readability score between a 6th-8th grade level. The team then consulted with an external readability expert well versed in revising informed consent documents into “plain language.” The resulting text was evaluated using Microsoft Word and an Online-Utility accessibility software. The final step involved adding visual images and graphics to complement the text. The Digital Health Checklist was then used to identify areas where the consent content could be expanded to address four key domains of Access and Usability, Privacy, Risks and Benefits, and Data Management. Results: The approved consent was evaluated at a 12.6 grade reading level, whereas the revised language by our study team received 12.4, 12, and 12.58 respectively. The final consent document synthesized the most readable of the three revised versions and was further revised to include language recommended by the software tool for improving readability, which resulted in a final revised consent readability score of a 9.2 grade level. Moreover, word count was reduced from 6424 in the original consent to 679 in the rewritten consent form. Conclusion: Utilizing an iterative process to design an accessible informed consent document is a first step in achieving meaningful consent to participate in research. This paper describes how a consent form approved by an ethics review board can be made more accessible to a prospective research participant by improving the document readability score and reducing the word count. Moreover, applying the Digital Health Checklist tool guided alignment with the four domains of Access and Usability, Privacy, Risks and Benefits, and Data Management.